Ethnomedicine and ethnobotany of Maerua subcordata (Gilg) DeWolf - Mebrahtom Gebrelibanos Hiben; Jochem Louisse; Laura H.J. de Haan; Ivonne M. C. M. Rietjens (Journal of Ethnic Foods, 2019)
Abstract Background Wild edible plants are valuable resources for improving food and nutritional security. Besides, they may provide important health benefits since the health-promoting components of plant-based foods usually exist at higher levels in wild plants. As a result, they are being sought as under-exploited potential sources of a health-promoting diet or a possible strategy to develop novel foods. In such exploration, ethnobotanical and ethnomedicinal data offer a fundamental step. The present study provides ethnomedicinal data on Maerua subcordata (Gilg) DeWolf (Capparidaceae). Methods The ethnomedicinal data was collected from the Kunama ethnics of northern Ethiopia via focus group discussion and oral interview. Supporting ethnobotanical data from relevant literature was also compiled and systematically reviewed. Results The results show that M. subcordata tuber is used by the Kunamas to manage malaria, malaria symptoms (fever, pain, gastrointestinal disorders), and seasonal cough while leaves are used for wound healing. In east Africa, its triple potential use as water purifying agent, food item, and herbal medicine was specified. As a herbal medicine, the tuber is used to manage a wide range of disorders including pain, infections, wounds, diabetes, blood pressure, and loss of appetite. Its use as laxative and abortifacient was also indicated. Leaves are used to treat wounds and ophthalmic and respiratory problems. As a food item, fruits are eaten during times of both food scarcity and food abundance while the tuber is used as a famine food. Conclusion In East Africa, M. subcordata represents a wild food and medicinal plant, which may be developed into a functional food.